Identification of a novel RSPO1-NUMT insertion in a LUAD patient cohort and the challenges and insights into NUMT detection highlighting the importance of reference genomes and population databases - Tietzová, Ilona; Sochorova, Dana; Triska, Petr; Rancourt, Rebecca C.; Omelka, Marek; Parobkova, Eva; Allgäuer, Michael; Schneider, Marc; Senghas, Karsten; Klotz, Laura Valentina; Tesarova, Marketa (Translational Lung Cancer Research, 2025)
Nuclear mitochondrial DNA sequences (NUMTs) represent mitochondrial DNA fragments integrated into the nuclear genome with potential clinical significance particularly in the pathology of cancer which have be identified in recent whole-genome sequencing (WGS) studies. Combining NUMT in silico analysis on WGS from The Cancer Genome Atlas with further characterize with molecular-genomic experiments (PCR assay and sequencing) across lung adenocarcinoma (LUAD) patient cohort tumor samples and incorporating important clinical parameters. Our molecular analysis of 298 LUAD samples revealed a RSPO1 gene NUMT insertion in approximately 31% of cases (29% heterozygous, 2% homozygous). This RSPO1-NUMT insertion’s presence was observed across matched blood, healthy lung, and tumor samples confirming its germline origin. Notably, homozygous carriers exhibited significantly earlier disease onset (mean age: 54 vs. 63.3 years; P=0.04) and a trend toward advanced-stage disease at diagnosis compared to no NUMT-insertion or heterozygous individuals. We report a novel NUMT insertion of the RSPO1 gene, which is a key regulator in the oncogenic WNT signaling pathway. Our findings also highlight technical challenges in NUMT detection across genome builds and databases, with significant discrepancies observed between reference genomes and population frequency estimates. We propose that this homozygous RSPO1-NUMT insertion may represent a previously unrecognized predisposing factor for LUAD development and progression through modulation of RSPO1 expression and subsequent WNT pathway activation, potentially influencing tumor vascularization, drug response, and disease progression.